Symptoms associated to boron deficiency in the oil palm (Elaeis guineensis Jacq.) in Costa Rica. - Gutiérrez-Soto, Marco V. (2013)
The objective of this work is to summarize the physiological and eco-physiological information relative to the functions, availability, economy and deficiency of boron in plants, with emphasis on the oil palm growing in Coto, Costa Rica. General aspects of boron chemistry in soils and plants are outlined, and its possible structural, metabolic and morphogenetic roles are discussed. The roles of boron in plant cell wall formation and stability, sugar transport, control of auxin levels, and reproductive development are discussed. The relative susceptibility of leaves and roots to boron deficiency are also compared. Boron deficiency symptoms observed in the oil palm are discussed, the possible causal mechanisms are outlined, and appropriate methods for deficiency corrections are mentioned. Therapies and chemical formulations and agronomic practices available for correcting boron deficiency and grant proper boron nutrition are presented.